Challenges of novice school principals: initial professional development and leadership - Sandoval-Estupiñán, Luz Yolanda; Sandoval-Estupiñán, Luz Yolanda; Pineda-Báez, Clelia; Bernal-Luque, Marlene del Rosario; Quiroga, Crisanto (Revista Complutense de Educación, 2020)
This research responds to the need to examine in depth the problems faced by novice principals in Latin America and to determine their professional development needs. Framed in a qualitative descriptive and interpretative study, interviews were carried out with novice principals in Colombia, where research about school principals is scarce. The study aims to describe and analyze the difficulties of a group of novice principals in their first years in their jobs. The results show that the complexity and peculiar characteristics of each institution, given by the context, the lack of financial resources and trained support teams in different management areas, coupled with gaps in principals’ preparation, outweigh their good intentions and limit the time they devote to their work. The study proposes to develop a leadership that enables novel principals to incorporate the systemic characteristics of people, institutions and contexts in their decision-making processes. I also highlights the need to foster in preparation programs the search for complete and integrative explanations to seek effective responses to the complex, dynamic school realities.